Measurement of branching fraction ratios for B + → D *+ D − K + , B + → D *− D + K + , and B 0 → D *− D 0 K + decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2020)
A measurement of four branching-fraction ratios for three-body decays of B mesons involving two open-charm hadrons in the final state is presented. Run 1 and Run 2 pp collision data are used, recorded by the LHCb experiment at centre-of-mass energies 7, 8, and 13 TeV and corresponding to an integrated luminosity of 9 fb−1. The measured branching-fraction ratios areBB+→D∗+D−K+BB+→D¯0D0K+=0.517±0.015±0.013±0.011,BB+→D∗−D+K+BB+→D¯0D0K+=0.577±0.016±0.013±0.013,BB0→D∗−D0K+BB0→D−D0K+=1.754±0.028±0.016±0.035,BB+→D∗+D−K+BB+→D∗−D+K+=0.907±0.033±0.014,$$ {\displaystyle \begin{array}{c}\frac{\mathcal{B}\left({B}^{+}\to {D}^{\ast +}{D}^{-}{K}^{+}\right)}{\mathcal{B}\left({B}^{+}\to {\overline{D}}^0{D}^0{K}^{+}\right)}=0.517\pm 0.015\pm 0.013\pm 0.011,\\ {}\frac{\mathcal{B}\left({B}^{+}\to {D}^{\ast -}{D}^{+}{K}^{+}\right)}{\mathcal{B}\left({B}^{+}\to {\overline{D}}^0{D}^0{K}^{+}\right)}=0.577\pm 0.016\pm 0.013\pm 0.013,\\ {}\begin{array}{c}\frac{\mathcal{B}\left({B}^0\to {D}^{\ast -}{D}^0{K}^{+}\right)}{\mathcal{B}\left({B}^0\to {D}^{-}{D}^0{K}^{+}\right)}=1.754\pm 0.028\pm 0.016\pm 0.035,\\ {}\frac{\mathcal{B}\left({B}^{+}\to {D}^{\ast +}{D}^{-}{K}^{+}\right)}{\mathcal{B}\left({B}^{+}\to {D}^{\ast -}{D}^{+}{K}^{+}\right)}=0.907\pm 0.033\pm 0.014,\end{array}\end{array}} $$
Im Titel ist [ast] als Tropfensternchen (englisch: teardrop-spoked asterisk) dargestellt
Im Titel sind "0", "[ast]", "-", "+" jeweils hochgestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, G. Frau, D. Gerick, J. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, S. Neubert, A. Piucci, M. Sarpis, N. Skidmore, S. Stemmle, D.A. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 22.02.2021